CONCEPT OF ILLICIT ENRICHMENT APPLICATION COMPARISON BETWEEN INDONESIA AND AUSTRALIA - Permata, Virna Amalia Nur; Aji Lukman Ibrahim (Awang Long Law Review, 2025)
This study aims to compare the application of illicit enrichment regulations and concepts between Australia and Indonesia and their implications in reducing corruption cases in both countries. The research method used is normative legal research with a Statute Approach, Conceptual Approach, and Comparative Approach. The legal materials used include primary legal materials, namely laws and regulations relevant to the issues under study. In addition, secondary legal materials consist of textbooks discussing various legal issues, scientific journals, works from legal circles, and research results. Tertiary legal materials are used as supplements, namely through the Internet. The data collection method used is library research. The results of the study show that illicit enrichment will be a breakthrough in the anti-corruption system in Indonesia. Although Indonesia has ratified the UNCAC, this ratification does not accommodate the concept of illicit enrichment. so that implementing illicit enrichment can be a good step, reflecting on Australia's success in indicating corruption earlier by looking at the increase and/or imbalance between the wealth of state officials and their legitimate income. In its implications, the Anti-Corruption Law can be the right legal framework for injecting the concept of illicit enrichment.